Oral Health Care of People with Disabilities - A Challenge in Dental Education in Georgia - Gigineishvili, Elene; Nikoleishvili, Elza (European Scientific Journal, ESJ, 2022)
Introduction: The dental caries and periodontal disease are the most prevalent diseases in people with disabilities. In 2014 The Association for Dental Education in Europe set up a special interest group to develop the field “Special Care dentistry”, which provides oral care services for people who are unable to accept routine dental care. Aim: This article aims to substantiate the role of implementation “Special Care Dentistry” in the dental curriculum and describes the importance of continuing medical education for the dentists, to provide equal and adequate dental services to the people with disabilities in Georgia. Methods: The first part of research was based on the analysis of the secondary data for identification the structure of the dental education programs of Georgian higher education institutions; A quantitative and qualitative data was analyzed among 160 people with disability through a specially designed questionnaire, deep interviews were conducted with participants, dentists, and managers of dental clinics. Results: 25% of Dental Clinic Managers reported, that their clinics are adapted for people with disabilities. Dental caries 18%, missed tooth due to caries 24% and gingival bleeding was detected in 47.8% of study participants, among them 10.6% outlined the lack of doctor qualifications and experience. Discussion: Provision comprehensive dental services to people with disabilities remain a significant challenge for dental clinics. A small number of dentists in Georgia have completed a continuing medical education course in special care dentistry. Conclusions: The oral health of people with disabilities in Georgia is unsatisfactory. More affords should be performed to implement “Special Care Dentistry” in dental education in Georgia.